Extended and direct evaluation of RT‐QuIC assays for Creutzfeldt‐Jakob disease diagnosis. Issue 2 (27th December 2016) - Groveman, Bradley R.; Orrú, Christina D.; Hughson, Andrew G.; Bongianni, Matilde; Fiorini, Michele; Imperiale, Daniele; Ladogana, Anna; Pocchiari, Maurizio; Zanusso, Gianluigi; Caughey, Byron
Abstract: Real‐Time Quaking‐Induced Conversion (RT‐QuIC) testing of human cerebrospinal fluid (CSF) is highly sensitive and specific in discriminating sporadic CJD patients from those without prion disease. Here, using CSF samples from 113 CJD and 64 non‐prion disease patients, we provide the first direct and concurrent comparison of our improved RT‐QuIC assay to our previous assay, which is similar to those commonly used internationally for CJD diagnosis. This extended comparison demonstrated a 21% increase in diagnostic sensitivity, a 2‐day reduction in average detection time, and 100% specificity.